TINJAUAN SIYÄ€SAH TANFÄªDZIYYAH TERHADAP TRANSFORMASI PENGAWASAN DIGITAL PADA PEMBAHARUAN DATA PEMILIH - Novalia, Sisca (Universitas Khairun, 2024)
Elections are a real manifestation of people's sovereignty within the framework of the Unitary State of the Republic of Indonesia. carried out by holding direct, public, free, secret, honest and fair voting based on the principles of Pancasila. Based on the Republic of Indonesia General Election Supervisory Agency (Perbawaslu) Regulation Number 4 of 2023 concerning Supervision of Data Updates and Preparation of Voter Lists in Elections, digital transformation is an addition to access to Bawaslu services in the performance of receiving reports, supervising the process in Elections, as well as a means of updating socialization and performance Bawaslu supervision. The problem formulation in this research is; 1) What is the form of Digital Supervision Transformation in Updating Voter Data, and 2) How does SiyÄsah TanfÄ«dziyyah's perspective view the practice of digital surveillance transformation in updating voter data.The research method used is qualitative with the type of field research (field research) and this research is descriptive analysis. The data collection method in this research is based on library research and uses secondary data. The aim of this research is to determine the transformation of digital supervision in updating voter data carried out by Bawaslu of Lampung Province. Second, to find out SiyÄsah TanfÄ«dziyyah's perspective on transforming digital election supervision by updating voter data and compiling voter lists carried out by Bawaslu. This research concludes that Bawaslu carries out supervision through digital media, including in the context of providing education to the public. Bawaslu's involvement in supervision attached to the KPU must be in accordance with Law Number 7 of 2017 concerning Elections in preparing programs and the priority scale for developing an open and participatory supervision system. The implementation of digital supervision transformation in updating data selection has not been fully maximized because several factors are needed. SiyÄsah TanfÄ«dziyyah's review of the transformation of digital supervision of the general election stages related to updating voter data is a form of supervision to uphold the benefit of the people in accordance with the objectives of MaqÄsid SyarÄ«'ah.